Practice of Religious Moderation in Islamic Education Through the Engagement of Organizations and Civil Society in Indonesia - Sugito Sugito; Mas'udi Mas'udi; Handaru Kusbiantoro (Fitrah: Journal of Islamic Education, 2026)
Religious moderation is a critical issue in pluralistic societies and relates not only to theological understanding but also to social practices in community life. This study aims to analyze the practice of religious moderation from the perspective of Islamic Religious Education within the Hidayatullah Islamic organization. The study employs a qualitative approach using the case study method. Data were collected through in-depth interviews, observations, and documentation involving organizational leaders, educators, cadres, social volunteers, and the community. The results indicate that religious moderation is realized through a cadre development system, education, social activities, economic empowerment, and dialogical da’wah. The cadre development system functions as character education that fosters discipline, social responsibility, and community commitment. Educational institutions serve as spaces for fostering tolerance and inclusive interaction within a pluralistic society. Additionally, social and economic programs strengthen social solidarity and enhance public trust in the organization. This study confirms that Islamic organizations play a crucial role in strengthening social cohesion and the practice of religious moderation within society.